(untitled) (Scientific journal of the Fergana State University, 2023)
The article studies the gathering process of fiber-separated seeds in the roll center while cotton ginning. At the same time, it studies the reasons of the cleaned seeds gathering in the roll box center and the effect of roll density on its weight. It gives recommendations on how to remove cleaned seeds from roll more quickly